PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) TERHADAP HASIL BELAJAR SISWA PADA KOMPETENSI TEKNIK DAN DESAIN NAIL ART DI SMK NEGERI 3 KEDIRI - Khilyatut Taqiyyah; Mutimmatul Faidah; Maspiyah; Sri Dwiyanti (Program Studi Pendidikan Tata Rias, 2025)
The purpose of this research is to examine the effects of a project-based learning paradigm on the competencies necessary for engineering and designing nail art. This research sets out to answer three questions: 1) how the project-based learning model was put into practice; 2) what students learn in terms of nail art engineering and design abilities; and 3) how students felt about the approach overall. The methodology used is a one-shot case study based on quantitative research methods and the pre-experimental design. Methods such as observation, posttests, and questionnaires are used to collect data. Descriptive statistical tests of the mean are used in data analysis procedures. Individuals participating in this research were high school seniors from SMK Negeri 3 Kediri's Beauty 2 class. The study's findings revealed the following: 1) Project-based learning was deemed very good overall with an average score of 4 aspects; 2) Class XI Beauty 2 students' learning outcomes regarding nail art technique and design material received an average score of 88, also classified as very good; 3) A total of 89.2% of students rated their experience with the project-based learning model as very good. The study's findings support the idea that SMK Negeri 3 Kediri's project-based learning methodology is a good fit for teaching students about nail art and design. Key Word : Project based learning model, learning outcomes, nail art technique and design competencies